Reduction of residual chlorpyrifos on harvested bird chillies (Capsicum frutescens Linn.) using ultrasonication and ozonation - S. Pengphol (2018)
Reduction of chlorpyrifos using ultrasonication, ozonation and a combination of ultrasonication and ozonation was investigated. A standard chlorpyrifos at the concentration of 1 mg l-1 was subjected to different frequencies at 108, 400, 700 and 1000 kHz, as well as ozone at the concentration of 25 ml min-1 with various exposure times (0, 10, 20, 30, 40, 50 and 60 min). It was found that ultrasonication at 1000 kHz for 60 min was the most effective treatment for reducing chlorpyrifos. In addition, ozone could reduce the concentration of standard chlorpyrifos after increased exposure time to 60 min. Ultrasonication in combination with ozone had a synergistic effect in reducing standard chlorpyrifos concentration with the highest rate of reduction occurring within the first 10 min. The standard chlorpyrifos was reduced 75.18% after ultrasonication at 1000 kHz and exposure to ozone for 60 min. The effectiveness of ultrasonic and ozone washing for reduction of chlorpyrifos residues on Bird chillies (Capsicum frutescens Linn.) were also determined by GC-FPD. The chlorpyrifos residue on fresh chillies after ultrasonic and ozone washing was reduced 73.03% after 60 min. The present study demonstrates that ultrasonication and ozonation are effective processes for the reduction of chlorpyrifos residues from aqueous solution and chlorpyrifos treated Bird chillies.